2021
DOI: 10.52134/ueader.889204
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Coping Strategies in the Relationship between Cognitive Flexibility and Well-being

Abstract: The purpose of this study is to explore the effects of cognitive flexibility on the five EPOCH well-being components: engagement, perseverance, optimism, connectedness and happiness. The study also investigates the mediating roles of coping strategies (i.e., active coping strategy, avoidant coping strategy, and negative coping strategy) in this relationship. The participants consisted of 488 high school students. The data were collected through Cognitive Flexibility Scale, KIDCOPE, and EPOCH. The results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 57 publications
0
3
0
2
Order By: Relevance
“…The model showed that cognitive flexibility and critical thinking increase academic motivation and reduce the effect of fear of negative evaluation on academic motivation. In addition, studies show that increased cognitive flexibility is associated with positive psychological outcomes (Asıcı & Sarı, 2021; Demirtaş, 2020; Doğan Laçin & Yalçın, 2019; Esen et al, 2017). Fear of negative evaluation is associated with psychological issues (Wang et al, 2012; Wells et al, 1995; Wolniewicz et al, 2018) and indirectly contributes to its relationship with cognitive flexibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The model showed that cognitive flexibility and critical thinking increase academic motivation and reduce the effect of fear of negative evaluation on academic motivation. In addition, studies show that increased cognitive flexibility is associated with positive psychological outcomes (Asıcı & Sarı, 2021; Demirtaş, 2020; Doğan Laçin & Yalçın, 2019; Esen et al, 2017). Fear of negative evaluation is associated with psychological issues (Wang et al, 2012; Wells et al, 1995; Wolniewicz et al, 2018) and indirectly contributes to its relationship with cognitive flexibility.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show a positive correlation between cognitive flexibility and critical thinking (Çuhadaroğlu, 2013), so as critical thinking skill increases, cognitive flexibility also increases. Moreover, increased cognitive flexibility is associated with positive psychological outcomes (Mellor et al, 2003) including self‐efficacy and mental well‐being (ASICI & SARI, 2021; Demirtaş, 2020; Doğan Laçin & Yalçın, 2019; Esen et al, 2017), critical thinking (Çuhadaroğlu, 2013), happiness (Asıcı & İkiz, 2015), life satisfaction (Çıkrıkçı, 2018; Odacı & Cikrikci, 2019), hope (Muyan‐Yılık & Demir, 2020). In addition, academic self‐efficacy mediates cognitive flexibility and mental well‐being (Demirtaş, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Alanyazında eğitim kurumlarında eğitim yöneticileri ve öğretmenler arasındaki ilişkileri farklı unsurlar açısından inceleyen çalışmalar yer almaktadır. Ekici (2020) ilkokul yöneticileri ile öğretmenler arasındaki iletişim durumları incelediği çalışmasında hem yöneticiler hem de öğretmenlerin konuya ilişkin görüşlerine başvurmuştur. Çalışma sonuçlarına göre yöneticinin öğretmenlerine görev verirken kullandığı iletişim dili öğretmenlerin üzerinde oldukça etkilidir.…”
Section: Araştırmanın Beşinci Alt Problemine İlişkin Tartışmaunclassified
“…elde ettiği sonucun öğretmenlerin örnek oldukları bulgusu ile paralellik gösterdiği belirtilebilir. Ekici (2020), yaptığı çalışmasında öğretmenlerin yöneticileri ile olan iletişimlerini değerlendirmiş ve öğretmenlerin sohbet havasında iletişim kurmalarını, kişisel konuları konuştuklarını, yardımlaştıklarını belirtmiş ve öğretmenleri olumlu etkilediği sonucuna ulaşmıştır. Bu sonuç öğretmenlerin meslektaşları ile iyi iletişimleri olduğu sonucu ile paralellik göstermektedir.…”
Section: Tartışma Ve Sonuçunclassified
“…When the authentic leadership characteristics of classroom teachers were evaluated from the eyes of their students, it was concluded that their communication was strong and their teachers were exemplary individuals for them. In his study, Ekici (2020) evaluated the communication of teachers with their administrators and stated that teachers communicate in a conversational mood, talk about personal issues and help each other, and concluded that it affects teachers positively. concluded in their study that the horizontal relationship between teachers is strong and it is done freely.…”
Section: Extended Summarymentioning
confidence: 99%